DIGITALIZATION AS A FACTOR IN ENSURING SUSTAINABLE DEVELOPMENT OF AGRICULTURE (American Journal of Interdisciplinary Research and Development, 2024)
In modern conditions, it is difficult to imagine the development of the economy without digitalization, without the implementation of digital transformation. Digital transformation is A process that an organization applies to embed digital technologies in all areas of its business, fundamentally changing the potential of its services for customers. The article reveals the need for the use of digital technologies in agriculture and the content of the processes taking place in the republic in this direction.